1988
DOI: 10.1093/clinchem/34.10.2096
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of a specific pancreatic isoamylase assay based on a double monoclonal-antibody technique.

Abstract: Eleven evaluators from nine laboratories in five countries evaluated a new immunoinhibition method for pancreatic isoamylase determination that is as simple to perform as that for total amylase. The precision at low and intermediate activity concentrations was superior, and at high concentrations it equalled that of the wheat-germ inhibitor method. The test was linear to approximately 2000 U/L, depending on the instrumentation used. The percentage salivary isoamylase activities remaining in specimens after rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Pancreatic isoamylase was determined on a Cobas-Bio (Roche Diagnostic Systems, Montclair, NJ) using the Boehringer Mannheim (Indianapolis, IN) enzymatic colorimetric test, pancreatic alpha-amylase p-nitrophenylmalthoheptaoside. 9 In this assay, the activity of human salivary isoamylase is inhibited by a monoclonal antibody that does not affect pancreatic isoamylase. The activity of pancreatic isoamylase is then measured at 37°C using a p-nitrophenyl-D-maltopeptaoside substrate.…”
Section: Patientsmentioning
confidence: 99%
“…Pancreatic isoamylase was determined on a Cobas-Bio (Roche Diagnostic Systems, Montclair, NJ) using the Boehringer Mannheim (Indianapolis, IN) enzymatic colorimetric test, pancreatic alpha-amylase p-nitrophenylmalthoheptaoside. 9 In this assay, the activity of human salivary isoamylase is inhibited by a monoclonal antibody that does not affect pancreatic isoamylase. The activity of pancreatic isoamylase is then measured at 37°C using a p-nitrophenyl-D-maltopeptaoside substrate.…”
Section: Patientsmentioning
confidence: 99%
“…We did not perform an analysis of amylase isoenzyme by the electrophoretic method, but pancreatic amylase, not total amylase, was assayed by a enzymatic photometric test, which is based on the method of monoclonal antibodies to inhibit the salivary enzyme and which distinguish pancreatic and salivary amylase sufficiently 17 , 18) . Therefore, it could be suggested that the pancreatitis was caused by the pheochromocytoma in our case.…”
Section: Discussionmentioning
confidence: 99%
“…В качестве биоматериала использовали 73 обезличенных образца сыворотки крови с различной активностью и изоферментным составом α-амилазы, которые были получены от доноров и хранились не более 14 дней при температуре -20 °С [18]. Степень ингибирования слюнной α-амилазы оценивали с применением образцов препаратов слюнной α-амилазы (Sigma, США) [19]. Для уточнения линейного диапазона измерения активности фермента реагентами с GalG 2 CNP использовали препарат α-амилазы «α-amylase from hog pancreas» (Fluka, Швейцария) с начальной общей активностью 46,4 кЕД/л.…”
Section: материал и методыunclassified